PHYLOGENETICS ANALYSIS OF MARINE AND COASTAL SPECIES USING 18S rRNA SEQUENCE - Shabarni Gaffar -; Linawati Hardjito -; Endang Srieatimah - (Bionatura, 2009)
Phylogenetics analysis using 18S rRNA sequence was done on some marine and coastal organisms that have been used as traditional medicine in Indonesia. Proper and accurate identification of coastal and marine organisms producing bioactive compound is important to support drug discovery. Ribosomal RNA has been described as one of most useful and most used for molecular chronometer. In this experiment a part of 18S rRNA gen was amplified using PCR employing 300F and 1400R primers. PCR product then was cloned using pGEM-T vector (Promega) and transformed into Eschericia coli. The recombinant Eschericia coli were sequenced by applying universal primer and internal primer. The alignment of sequenced product and phylogenetic analysis indicated that sample 1 closely related to Chaetomorpha crassa, sample 2 closely related to Ptilophora pinnatifida, sample 3 closely related to Flagellaria indica, and sample 4 closely related to Wallemia ichthyophaga. Keywords: phylogenetic analysis, 18S rRNA sequence.